Multi-objective optimization of pyroelectric thermal–electrical cycles - Dip Dutta; Haopeng Zhang; Bikram Bhatia (AIP Advances, 2022)
Pyroelectric thermal–electrical cycles enable a class of solid-state heat engines that convert waste heat to electrical energy. This article numerically investigates thermal-to-electrical energy conversion in a PbZr0.52Ti0.48O3 (PZT) pyroelectric layer near room temperature and optimizes operating parameters to maximize the electrical energy output. A general thermodynamic cycle is modeled after the prototypical pyroelectric Ericsson cycle—implemented based on the Ginzburg–Landau–Devonshire theory—with variable operating temperature range, and heating/cooling and charging/discharging time intervals. We used a Pareto optimization approach to simultaneously maximize electrical energy density and power density for different PZT sample and cycle parameters. The evaluated Pareto optimal fronts showcase the possibility of achieving multiple optimal solutions and highlight the trade-off between output energy density and power density in pyroelectric energy conversion. Specifically, we demonstrate that a 4× enhancement in power density is achievable with a less than 10% reduction in energy density for the same sample and operating conditions primarily by optimizing heat transfer. The multi-objective optimization approach and results presented in this study could provide a framework to facilitate the design and operation of pyroelectric cycles for waste heat energy harvesting systems.